From the social and solidarity economy to economic solidarity: transitions toward cooperative knowledge - Saez Riquelme, Felipe (Cooperativismo & Desarrollo, 2016)
Purpose: Looking at the experience of Argentina, this article intends to reflect on the ways in which the country’s social and solidarity economy has been conceptualized to date. Description: Based on the analysis of various foundational texts in this field and synthesis of part of my previous research, I would like to arguethat the approaches to the study of these socioeconomic experiences represent a Eurocentrism in the knowledge. This is based on what I have called distance methodologies, i.e., ways of knowing that bypass power relations and decontextualize local knowledge in the interest of generating common criteria for general analysis. Viewpoint: These methods represent an exercise of epistemic violence and produce historical silences. Conclusions: Following Trouillot’s contention regarding the relationships between power and history production, that which hasbeen seen in this field of knowledge to date has closed off memories, histories, and knowledge located in economic/cultural difference. In order to recover these stories of other, I wish to share the contributions of the Andean Oral History Workshop to the creation of nearness methodologies, in a transition to knowledge characterized by cooperation and solidarity.
Keywords: coloniality of power; social and solidarity economy; methodology; economic solidarity; Andean oral history workshop